Evaluasi Kesesuaian Lahan Tanaman Palawija pada Lahan Kering di Kecamatan Gerokgak - Lestari, Mei Esra; Sumarniasih, Made Sri; Mega, I Made (Nandur, 2021)
This research aims to determine the land suitability class for secondary crops, limiting factors, improvement efforts and making land use maps. The crops evaluated included peanuts, sorghum, soybeans, corn. The research location was carried out in Gerokgak District, Buleleng Regency, Bali Province from December 2020 to February 2021. Based on the results of slope maps, soil type maps, and overlapping land use maps, 9 homogeneous lands were obtained. The research method used a survey method for land characteristics and for soil sampling, then soil analysis was carried out in the laboratory. The suitability of the land is carried out to the sub-class level, by comparing the characteristics of the assessment land with the conditions for growing existing plants. The results showed that the actual land suitability classes for maize, sorghum, soybeans, and legumes were S3 (Marginal Suitability) to N (Not Suitability); In SLH6, SLH 8, SLH 9 for maize, sorghum, soybeans, and peanuts are classified as N (Not Suitability) while in SLH  1, SLH 2, SLH 3 , SLH 4, SLH 5, SLH 7 belong to S3. General directions for land use that can be taken to increase land productivity in the research area are terracing, garden sanitation, fertilization using urea fertilizer and SP36.